2018
DOI: 10.1038/s41419-017-0028-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-term retinoic acid treatment sustains pluripotency and suppresses differentiation of human induced pluripotent stem cells

Abstract: Human pluripotent stem cells (hPSCs), including human embryonic stem cells (hESCs) derived from blastocyst and human induced pluripotent stem cells (hiPSCs) generated from somatic cells by ectopic expression of defined transcriptional factors, have both the ability to self-renew and to differentiate into all cell types. Here we explored the two antagonistic effects of retinoic acid (RA) on hiPSCs. Although RA has been widely described as a pharmacological agent with a critical role in initiating differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 40 publications
(48 reference statements)
6
30
0
Order By: Relevance
“…The RA-induced proliferation and survival of EB-forming cells led to a dramatic increase in the number of EBs. However, the generated EBs displayed a delayed differentiation in comparison to RA-untreated EBs, which agrees with a recent study showed that short RA exposure suppresses hiPSC differentiation by inhibiting Wnt canonical pathway [17].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The RA-induced proliferation and survival of EB-forming cells led to a dramatic increase in the number of EBs. However, the generated EBs displayed a delayed differentiation in comparison to RA-untreated EBs, which agrees with a recent study showed that short RA exposure suppresses hiPSC differentiation by inhibiting Wnt canonical pathway [17].…”
Section: Discussionsupporting
confidence: 92%
“…Although RA has been widely described as an inducer of cell differentiation, RA can antagonize cell differentiation and induce stemness depending on the concentration, time of exposure and cell type [16]. For example, while high RA concentrations induce the differentiation process of PSCs into pancreatic and neuronal cell lineages [17,18], short exposure of PSCs to low concentrations of RA sustains pluripotency and suppresses differentiation [17]. Surprisingly, comparably low concentrations of RA have been shown to promote differentiation of adipocytes from mouse ESCs [19]; however, the overall efficiency remains modest and the mode of control of these antagonistic effects of RA is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Cell lysates were prepared as previously described. 16 and acquired with UVITEC Imaging Systems. Actin (sc-1616, Santa…”
Section: Western Blotmentioning
confidence: 99%
“…ESCs and iPSC-1, we selected the RAR Activation signalling, as retinoids including Vitamin A and its derivatives have been widely associated with embryonic development and differentiation. 27,28 Here, we evaluated the effects on hESCs and hiPSC-1, -2, and -3 by immunofluorescence quantification, the hiPSCs lines (-1, -2, and -3) showed an enhanced expression of SOX17 when they were simultaneously exposed to RA and BMS493 (RA+/BMS493+) as shown by immunofluorescence ( Figure S3) and its quantification ( Figure 5C).…”
Section: Role Of the Rar Activation Pathway And Its Modulation On Tmentioning
confidence: 99%
“…Another pathway that resulted enriched PCR analysis. Among these exclusive pathways, we focused on the RAR Activation Pathway since Retinoic acid and its receptors are classically linked both to embryonic development43,44 and to pluripotency maintenance 28,45. Subtle regulation of RA signalling is fundamental for the PSCs in order to choose between self-renewal and differentiation programmes, as demonstrated by the fact that hESCs and hiPSCs behave differently when they undergo to treatment with Retinoic acid or BMS493.…”
mentioning
confidence: 99%